2006
DOI: 10.1177/0310057x0603400403
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes following a Shortage of High Dependency Unit Beds for Surgical Patients

Abstract: In an environment of resource rationing there are numerous patients who are unable to be admitted to a highdependency unit (HDU) postoperatively despite the belief that this is the optimal discharge destination for them from the recovery room. It is unknown if this is associated with an increase in adverse outcomes. We performed an observational study, over a two-month period, comparing outcomes between patients who were admitted to HDU postoperatively and patients who, although an HDU bed was preferred, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 20 publications
0
17
0
2
Order By: Relevance
“…The strengths of this study are that it is a multicentre, randomized clinical trial with a low risk of bias compared with previous studies. The complex intervention was described thoroughly before the start, good clinical practice monitors assessed adherence to the trial protocol, and the actual monitoring and treatment levels in the intervention groups were reported clearly, as recommended for non‐pharmacological trials.…”
Section: Discussionmentioning
confidence: 99%
“…The strengths of this study are that it is a multicentre, randomized clinical trial with a low risk of bias compared with previous studies. The complex intervention was described thoroughly before the start, good clinical practice monitors assessed adherence to the trial protocol, and the actual monitoring and treatment levels in the intervention groups were reported clearly, as recommended for non‐pharmacological trials.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar design McIlroy et al . [21] concluded that IC may lead to longer hospital stay, but no effect on 30-day mortality or all-cause morbidity could be shown. Jones et al .…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the impact of SDUs are limited to observational, single-center before/after reports with varying conclusions (9,38,(41)(42)(43)(44)(45)(46)(47). The majority of studies to date provide data on SDUs as a safe post-operative care option, with a particular emphasis on cardiothoracic surgery patients and safe reduction in time to extubation, reducing the need for full intensive care (39,43,44,(48)(49)(50)(51).…”
Section: Sdu Care and Patient Outcomesmentioning
confidence: 99%
“…Other studies have failed to find a mortality benefit attributable to the establishment of an SDU or SDU-level care itself (9,38,42,45). The ongoing InCare trial in Denmark is explicitly focused on mortality associated with postoperative SDU care versus ward care after major abdominal emergency surgery (54), and will be the first major multicenter trial evaluating outcomes attributable to different levels of postoperative care.…”
Section: Sdu Care and Patient Outcomesmentioning
confidence: 99%
See 1 more Smart Citation